Effects of riparian woody vegetation encroachment on prairie stream structure and function with emphasis on whole-stream metabolism - Riley, Alyssa J. (Kansas State University, 2011)
Much of the North American tallgrass prairie ecosystem has been converted to cropland or urbanized. One threat to the remaining prairie ecosystems, and the streams within, is woody vegetation encroachment. Stream productivity, measured as metabolism, is a fundamental process comprised of gross primary production (GPP) and (CR) community respiration. Understanding GPP and CR is important because these processes are vital to ecosystem function and can be impacted by a change in canopy cover. First, I investigated improvements in existing methods for estimating whole-stream metabolism as estimated from diel patterns of oxygen (O2). I compared measured and modeled O2 and aeration (a physical parameter required for measurement of metabolism) rates to determine if direct measurement of aeration is necessary and the importance of temperature correction of metabolism. Modeling was moderately successful in determining aeration rates, and temperature correction of GPP and CR substantially improved model fits. Second, effects of woody vegetation encroachment on prairie stream function were investigated. Stream metabolism was measured for four years in duplicate reaches with varying canopy cover (closed canopy, naturally open canopy, and vegetation removal reaches). The removal reaches had closed canopy for the first two years and open canopy for the last two years. Canopy cover increased CR rates and had minimal effects on GPP. Third, the same experiment was used to determine the effects of woody vegetation encroachment on prairie stream ecosystem structure and food web interactions. Chlorophyll a and filamentous algal biomass were greater in naturally open and vegetation removal reaches, although the effects were stronger on filamentous algal biomass. As canopy cover decreased, the filamentous algal biomass to chlorophyll ratio increased, indicating a shift in algal community structure. Stable isotope analysis indicated some shift in pathways of nitrogen and carbon flux into the food web related to degree of canopy cover, but overlap in the signature of food sources made distinct food sources difficult to identify. The data indicate that riparian encroachment can influence ecosystem structure and function in prairie streams and restoration to remove woody riparian cover may restore some ecosystem features of naturally open canopy streams.
Keywords: streams; metabolism; canopy; Biology (0306); Ecology (0329)